A study on the maintenance management of food courts / Azam Mohamad. - Mohamad, Azam (2006)
There is a growing need and demand in food and beverage service in Malaysia. This can be seen from the emerging of eating venues that come in the form of restaurant, food court and stalls. The study focuses on the Klang Valley area only in order to limit the scope of the study. To support this research, four numbers of food courts were selected as case studies. The primary and secondary data were gathered from questionnaire surveys, observation and interviews conducted as well as references to the published reports, seminars papers and published books. It can be summarized that the maintenance management of food courts are not being progressively undertaken and performed due to non-existence of a quality standard guideline for the maintenance works, programme and the failure to set up an appropriate maintenance management to oversee the implementation of the maintenance works. Lack of supervision and inspection is another contributing factors on the failure of carrying out appropriate and standardized maintenance works. Maintenance management of a food court in Malaysia is carried out in a general manner rather than intuitive and progressive schedule. In addition, the opinions of maintenance management implementation and quality standard were gathered through structured interview and the results were then critically analyzed. From the findings, the author hopes that the research would give clear perception to the reader on the current practice of maintenance management and its implementation in the local market. It is recommended that a research on the same topic to be undertaken on other municipalities. In addition to this, detailed studies on the frequency of maintenance works, procedures on the maintenance works carried- out and quality assurance or inspection (QA/QC) to be also included.